2016
DOI: 10.18632/oncotarget.12439
|View full text |Cite
|
Sign up to set email alerts
|

Kindlin-2 interacts with β-catenin and YB-1 to enhanceEGFRtranscription during glioma progression

Abstract: Kindlin-2 promotes carcinogenesis through regulation of cell-cell and cell-extracellular matrix adhesion. However, the role of Kindlin-2 in glioma has not been elucidated. We investigated Kindlin-2 expression in 188 human glioma tissue samples. High Kindlin-2 expression was correlated with high pathological grade and a worse prognosis. Kindlin-2 promoted glioma cell motility and proliferation both in vitro and in vivo. Importantly, Kindlin-2 activated the EGFR pathway and increased EGFR mRNA levels. In additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 50 publications
2
22
0
Order By: Relevance
“…Previous studies indicated that EGFR inhibitor markedly diminished EGFR phosphorylation in a dose‐dependent manner and suppressed proliferation of the chordoma in vitro and vivo . EGFR was transcriptionally induced by YBX1 in breast cancer and glioma . In our study, immunohistochemical staining showed that YBX1 expression was correlated to p‐EGFR and p‐Akt expression in chordoma.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…Previous studies indicated that EGFR inhibitor markedly diminished EGFR phosphorylation in a dose‐dependent manner and suppressed proliferation of the chordoma in vitro and vivo . EGFR was transcriptionally induced by YBX1 in breast cancer and glioma . In our study, immunohistochemical staining showed that YBX1 expression was correlated to p‐EGFR and p‐Akt expression in chordoma.…”
Section: Discussionsupporting
confidence: 66%
“…As in breast cancer and glioma. 18,19 In our study, immunohistochemical staining showed that YBX1 expression was correlated to p-EGFR and p-Akt expression in chordoma. These data supported the hypothesis that YBX1 was involved in chordoma development through the EGFR pathway.…”
Section: Ybx1 Promotes Chordoma Tumor Growth In Vivosupporting
confidence: 53%
See 2 more Smart Citations
“…Interestingly, Yu and coworkers showed that Kindlin-2 binds to β-catenin to promote tumor cell invasion and progression. 36,37 Likewise, Lin et al showed that Kindlin-2 accelerates hepatocellular carcinoma invasion and metastasis by upregulating Wnt/β-catenin signaling. 38 Thus, Kindlin-2 can upregulate β-catenin through interactions with the latter and through an indirect mechanism involving sclerostin downregulation.…”
Section: Discussionmentioning
confidence: 99%